Tax Audit, Deterrence, And In-House Tax Professionals’ Tax Compliance : Empirical Evidence from Malaysia - Nivakan, Sritharan; Salawati, Sahari; Sharon Cheuk, Choy Sheung; Ahmad Syubaili, Mohamed (UNISZA, 2023)
The hitherto published studies have not yet explored the tax compliance behaviour of in-house tax professionals. It is assumed from the literature reviews on taxation that a tendency for tax non-compliance exists among the professionals who deal in tax matters in their business establishments when they do not comply with their respective tax systems. Deterrence theory suggests the tax audit or probability of getting audited influences an individual compliance pattern. Given this gap in the literature, this study endeavours to investigate the tax audit impact on Malaysian in-house tax professionals’ tax compliance behaviour. Using purposive and snowball sampling techniques, the data was collected from 392 in-house tax professionals of businesses in Malaysia. SmartPLS is used to analyse the data and test the hypotheses. The findings of this study divulge probability of getting audited strongly impacts upon personal tax compliance of corporate in-house tax professionals. This study opens a gateway to producing extensive and expeditious empirical evidence that could support the relatedness between tax professionals’ personal tax compliance and their decision-making on corporate tax compliance.